Сезонність розмноження та його особливості у видів підродини Unioninae (Mollusca, Unionidae) фауни України - Янович, Лариса; Yanovich, Larisa (Східноєвропейський національний університет імені Лесі Українки, 2014)
Процеси розмноження у перлівниць із водойм та водотоків України перебігають неповноцінно, причиною чого припускають негативний вплив забруднювачів водного середовища та низьку щільність населення, що унеможливлює амфіміксис.Reproduction peculiarities in Unioninae subfamily species: Unio pictorum Linnaeus, 1758, U. tumidus Philipsson, 1788, U. crassus Philipsson, 1788 from water reservoirs and streams of river basins in Ukraine are established. In general, reproduction period in U. pictorum takes place from the end of spring-the beginning of summer to the autumn that is in the warmest period. The reproduction type in U. tumidus is characterized as in more cold-resistant species and differs from that of thermophilic U. pictorum. U. crassus reproduction in comparison with other unionids has the shortest duration. It is established that reproduction processes in these three Unioninae subfamily species are imperfect. Only in 17−27 % of collection points «gill pregnancy» was registered in 100 % of Unioninae females, as it was typical earlier. Partial (seldom complete) filling of marsupial with sex products or larvae was noted. The negative influence of water toxicants on gametogenesis and low population density which make amphimixis in animals with potentially separate sexes impossible are supposed to be the reasons of this phenomenon.
Seasonal Character of Reproduction and It’s Peculiarities in Unioninae (Mollusca, Unionidae) Subfamily Species in the Fauna of Ukraine
Keywords: перлівниці (Unioninae); розмноження; гаметогенез; нерест; unionids (Unioninae); reproduction; gametigenesis; spawning